PENGARUH PENAMBAHAN HIDROKSIAPATIT DAN KITOSAN PADA PLA DAN ABS TERHADAP SIFAT MEKANIK DARI KOMPOSIT BIOMATERIAL - I Wayan Gede Suputra Wardiana; Putu Hadi Setyarini; Teguh Dwi Widodo (Jurnal Rekayasa Mesin, 2022)
The purpose of this study is determine the mechanical properties of PLA-Hap-Chitosan and ABS-HAp-Chitosan composites. Poly lactic acid (PLA) and acrylonitrile butdie styrene (ABS) are polymers that can be applied in the biomedical field because they the to decompose naturally in the human body. To streng and not make the body wear out, a ceramic element that has bioactive, biodegradable and biocompatible properties is added, namely hydrochiapatite (HAp). In addition to hydroxyapatite, chitosan is also added as a natural element that has as an anti-bacterial. The materials used are PLA and ABS with variations using HAp powder and chitosan. The process of making this composite uses an injection molding process with a temperature of 190oC on PLA and 250oC on ABS. The results showed that the addition of HAp and chitosan powder to PLA and ABS caused a decrease in the mechanical properties of the composite, this was due to the difference in polarity which led to the formation of agglomeration in the composite and resulted in poor interactions, causing the mechanical properties of the composite to decrease. The maximum mechanical properties are aimed at the composition of PLA-Hap-Chitosan 90-0-10 and the minimum is PLA-Hap-Chitosan 90-2-8. Meanwhile, for the ABS-HAp-Chitosan composite, the maximum mechanical properties were aimed at the ABS-HAp-Chitosan 90-8-2 composition and the minimum for the ABS-Hap-Chitosan 90-0-10 composition.